Evaluation of the Anatomical Reference Point in Posterior Minimally Invasive Atlantoaxial Spine Surgery: A Cadaveric Anatomical Study - Peirong Lian; Hu Chen; Wanshun Wang; Changrong Zhu; Qiang Tu; Xiangyang Ma; Hong Xia; Honglei Yi (Orthopaedic Surgery, 2024)
Objective Minimally invasive atlantoaxial surgery offers the benefits of reduced trauma and quicker recovery. Previous studies have focused on feasibility and technical aspects, but the lack of comprehensive safety information has limited its availability and widespread use. This study proposes to define the feasibility and range of surgical safety using the intersection of the greater occipital nerve and the inferior border of the inferior cephalic oblique as a reference point. Methods Dissection was performed on 10 fresh cadavers to define the anatomical reference point as the intersection of the greater occipital nerve and the inferior border of the inferior cephalic oblique muscle. The study aimed to analyze the safety range of minimally invasive atlantoaxial fusion surgery by measuring the distance between the anatomical reference point and the transverse foramen of the axis, the distance between the anatomical reference point and the superior border of the posterior arch of the atlas, and the distance between the anatomical reference point and the spinal canal. Measurements were compared using Student's t test. Results The point where the occipital greater nerve intersects with the inferior border of the inferior cephalic oblique muscle was defined as the anatomical marker for minimally invasive posterior atlantoaxial surgery. The distance between this anatomical marker and the transverse foramen of the axis was measured to be 9.32 ± 2.04 mm. Additionally, the distance to the superior border of the posterior arch of the atlas was found to be 21.29 ± 1.93 mm, and the distance to the spinal canal was measured to be 11.53 ± 2.18 mm. These measurement results can aid surgeons in protecting the vertebral artery and dura mater during minimally invasive posterior atlantoaxial surgery. Conclusions The intersection of the greater occipital nerve with the inferior border of the inferior cephalic oblique muscle is a safe and reliable anatomical landmark in minimally invasive posterior atlantoaxial surgery.